The use of a non-integer order PI controller with an active queue management mechanism - Domański, Adam; Domańska, Joanna; Czachórski, Tadeusz; Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
In this paper the performance of a fractional order PI controller is compared with that of RED, a well-known active queue management (AQM) mechanism. The article uses fluid flow approximation and discrete-event simulation to investigate the influence of the AQM policy on the packet loss probability, the queue length and its variability. The impact of self-similar traffic is also considered.
Keywords: active queue management; PI controller; dropping packets; fractional calculus